Three new species of Nilothauma Kieffer (Diptera: Chironomidae) from Brazil - Dantas, Galileu P.s.; Hamada, Neusa (Zootaxa, 2017)
Three new species of Nilothauma from Brazil are described and illustrated based on adult males. Nilothauma paucisetis sp. nov. is similar to Nilothauma aripuanense Mendes & Andersen, 2009, but can be distinguished by the number of dorsal setae on tergite IX and by the shape of anal point. Nilothauma anamariae sp. nov. is easily recognized by having the inferior volsella L-shaped, with a long simple lateral bristle and an apical lobe directed inwards, bearing 10–12 apically split setae. Nilothauma jaquei sp. nov. is distinguished from all others congeneric species by the superior volsella without microtrichia, with one apical seta and a lateral spine.